Economic Problems Faced by Smallholder Workers in Plantation Sector: A Sociological Study Based on the Bogawanthalawa Area - Krishanthini, S; Ahilan, K. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
Among the leading foreign exchange-earning sectors in Sri Lanka, the plantation sector plays a significant role. Within this sector, smallholder estate workers have emerged as a prominent group contributing substantially to the country’s income. Following land reforms, over 75% of exports in the plantation sector were identified as coming from smallholder tea producers. This study aims to identify the economic problems faced by smallholder estate workers and the root causes of those problems. A descriptive cross-sectional mixed-method approach was adopted, and data were collected from 65 smallholder estate workers in the Kottiyagala and Selvakandai areas of the Bogawantalawa region, under the Nuwara Eliya District’s Norwood Divisional Secretariat. Both primary data (questionnaires, case studies, interviews, and focus group discussions) and secondary data (research articles and journals) were used. Data analysis was conducted using the SPSS-26 statistical software. The findings reveal several key issues: income insufficiency, lack of social support, absence of welfare benefits, increased debt, substandard living conditions, high interest rates, the exploitative role of intermediaries, poor productivity of tea bushes, inability to negotiate fair prices, economic double burden, supply chain inefficiencies, lack of technical knowledge, unstable tea pricing, high production costs, challenges in marketing, exploitation of retired women workers, climate variability, limited access to benefits, and job insecurity. Workers in the smallholder tea sector operate without formal job protection or welfare support and are entangled in internal political dynamics within the management system. The data confirm that smallholder tea estate workers in the study area face numerous economic challenges. To improve their livelihoods, local-level support mechanisms such as cooperative societies and labor unions must be strengthened. The government should formulate policies that create equitable environments for workers’ well-being, implement robust economic strategies, and establish a subsidized pricing system for tea.
Keywords: Smallholder tea estates; Supply chain; Double burden; Wage exploitation; Income insecurity; Debt